Class 1 major histocompatibility complex antigens on human extra-villous trophoblast. - Redman, C; Mcmichael, A; Stirrat, G; Sunderland, C; Ting, A (1984)
Using immunohistological techniques, class 1 products of the major histocompatibility complex (MHC) have been demonstrated on various forms of human extra-villous trophoblast in placental tissues taken from first, second and third trimester pregnancies. This contrasts with the absence of class 1 MHC antigens on all forms of villous trophoblast. The extra-villous trophoblast which reacted with antibodies to monomorphic class 1 MHC antigens consistently failed to bind HLA-A or HLA-B antibodies specific for the foetal phenotype. This suggests, but does not prove, that the MHC antigen expression of trophoblast may be restricted to HLA-C or some other undefined class 1 antigen.